Asymptomatic versus symptomatic atrial fibrillation: A systematic review of age/gender differences and cardiovascular outcomes - Xiong, Qinmei; Proietti, Marco; Senoo, Keitaro; Lip, Gregory Y.H. (International journal of cardiology, 2015)
Up to 40% of atrial fibrillation (AF) patients are asymptomatic. Despite this, scarce data are available about asymptomatic AF, with regard to its clinical profile and relationship to cerebrovascular and cardiovascular risks. Our objective was to conduct a systematic review and meta-analysis was to study the relationship between age and gender with asymptomatic AF and to establish whether patients with asymptomatic AF have a higher risk of death (all-cause and cardiovascular) and stroke/systemic thromboembolism, when compared to symptomatic AF patients. After a comprehensive search, 6 studies (2 randomized clinical trials and 4 observational studies) were entered in the meta-analysis. Despite significant heterogeneity, our data show that the prevalence of females amongst asymptomatic AF group was significantly less compared to the symptomatic AF group (RR, 0.57; 95% CI: 0.52–0.64). No difference in age between asymptomatic and symptomatic AF patients (P=0.72) was seen. No differences were found in all-cause death between patients with asymptomatic and symptomatic AF (RR, 1.38; 95% CI: 0.82–2.17), nor in cardiovascular death (RR, 0.85; 95% CI: 0.53–1.36) or stroke/thromboembolism (RR, 1.72 95% CI: 0.59–5.08). Asymptomatic AF is more associated with male sex, irrespective of age. Both general and cardiovascular death risks as well as thromboembolic risk do not seem to be affected by the asymptomatic clinical status. Symptomatic status should not determine our approach to stroke prevention and other cardiovascular prevention therapies, amongst patients with AF. •Asymptomatic atrial fibrillation (AF) is more associated with male sex, irrespective of age.•Asymptomatic clinical status doesn't seem to affect death risk as well as thromboembolic risk.•Clinical status shouldn't determine our approach to pharmacological prevention strategies.